Extension of time in commencement of arbitration proceedings - Noor Halwani Mokhtar, 1988-; Maizon Hashim, supervisor; Fakulti Alam Bina (2012)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2012